Public Sector Accounting, Financial Accountability and Viability in Times of Crisis
XXX, 279 p. 14 illus.
Keywords: “This book provides a rich account of the pervasive and important roles played by public sector accounting, financial management, auditing, and budgeting systems during the pandemic and also on the critical issues they may have raised, or not contributed to avoid”. - Ileana Steccolini, Professor of Accounting, University of Essex, UK This book examines the implications of the Covid-19 pandemic for public-sector accounting and finance. It provides a holistic overview of government initiatives to navigate the pandemic, focusing on how government policies and related spending have affected the budgetary process, the disclosure of information and transparency, as well as the importance of accounting technologies and operating systems in times of crisis. The book shows how government economic interventions have been crucial in counteracting the financial consequences of the global pandemic, and emphasizes the importance of accountability. It will appeal to students and scholars of public policy, public administration and finance, as well as policymakers and public managers responsible for public sector financial and budgetary reporting of public administrations. Giovanna Dabbicco is a Researcher at the National Statistical Office (ISTAT) of Italy. She was previously Adjunct Assistant Professor of Planning and Control in Public Administrations at University of Roma Tre, Italy. Her expertise is at the interface of accounting, statistics and management, in particular government accounting and national accounting. Giovanna Dabbicco is Researcher at the Italian National Statistical Office (ISTAT). She was formerly Adjunct Assistant Professor of Planning and Control in Public Administrations at University of Roma Tre, Italy. Marco Bisogno is Associate Professor in Accounting at the University of Salerno, Italy. Josette Caruana is Senior Lecturer in the Department of Accountancy at the University of Malta. Johan Christiaens is Professor in the Department of Accounting, Corporate Finance and Taxation at Ghent University, Belgium.